Association between intake of sweetened beverages with all-cause and cause-specific mortality: a systematic review and meta-analysis. (9th April 2021) - Li, Hongyi; Liang, Huoyan; Yang, Han; Zhang, Xiaojuan; Ding, Xianfei; Zhang, Ruifang; Mao, Yimin; Liu, Zhangsuo; Kan, Quancheng; Sun, Tongwen
ABSTRACT: Background: Conclusions remain controversial between the consumption of sugar and artificially sweetened beverages (SSBs and ASBs) and mortality. Methods: We systematically searched the PubMed, Embase, Cochrane Library and Web of Science databases from their inception date to 1st January 2020, prospective cohort studies researching the mortality risk and SSBs or ASBs consumption were included. Random effects meta-analyses and dose–response analyses were performed to measure the association. Subgroup analyses and sensitivity analyses were further performed to explore the source of heterogeneity. Publication bias was assessed by Funnel plots and Egger's regression test. Results: Across all 15 cohorts, 1211 470 participants were included. High SSB consumption was associated with a higher risk of all-cause mortality (hazard ratio [HR], 1.12; 95% confidence interval [CI], 1.06–1.19, P  < 0.001; and cardiovascular disease [CVD] mortality [HR 1.20, 95% CI, 1.05–1.38, P <  0.001]), and high ASBs consumption showed similar result (HR 1.12, 95% CI, 1.04–1.21, P  = 0.001 for all-cause mortality and HR 1.23, 95% CI, 1.00–1.50, P  = 0.049 for CVD mortality), both showed a linear dose–response relationship. Conclusions: High consumption of both ASBs and SSBs showed significant associations with a higher risk of CVD mortality and all-cause mortality. This information may provide ideas for decreasing the global burden of diseases by reducing sweetened beverage intake.